Reconstruction in Regulation of Castraction Punishment for Children Protection as Sexual Victim Based on Value Justice - Nursariani Simatupang; Mahmutarom HR; Sri Endah Wahyuningsih (International Journal Reglement & Society (IJRS), 2023)
The regulation of castration criminal sanctions for the protection of children as victims of sexual violence is not based on the value of justice. Castration punishment can only be imposed on perpetrators of child sexual violence who fall within the criteria determined by Article 81 paragraph (7). If it does not meet the existing criteria, castration cannot be imposed. This discriminatory attitude shows the government's lack of seriousness in making policies for child protection. Sexual violence against children is a very fatal crime, damaging the future of children and causing disgrace to this nation. For this reason, it is necessary to reconstruct the regulation of castration criminal sanctions in order to protect children as victims of sexual violence based on the value of justice. The reconstruction includes the reconstruction of values and the reconstruction of legal norms. The reconstruction of castration regulations aims to protect all children in Indonesia, especially children who are victims of sexual violence. So that children do not become victims of sexual violence again